Modeling the risk relationships and defining the risk set - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S.; Soh, B. (Universidad de Talca, 2005)
In a peer-to-peer financial transaction there is a possibility of the trusted peer engaging in an untrustworthy manner and in a negative behaviour on the buyer's expense resulting in the loss of the buyer's resources. This possibility of the loss in the buyer's resources is termed as Risk. Hence Risk analysis is important in a transaction to determine the likelihood of the loss in the resources involved in the transaction. We have developed a methodology by which the trusting peer can assign a Riskiness value to a trusted peer after the transaction hence knowing its Riskiness value. In this paper we represent the Risk relationship that a trusting peer has with a trusted peer after transacting with it and define a standard format for representing the Risk relationship so that when it gives a recommendation to any other trusting peer it is easier for them to interpret and understand.